Optimasi Parameter Mesin Laser Tube Cutting Terhadap Kekasaran Permukaan Dan Laju Pemotongan Pada Square Pipe ST 37 Menggunakan Taguchi Grey Relational Analysis Method - Lintang Aditya Wardani; Farizi Rachman; Pranowo Sidi (Proceedings Conference On Design Manufacture Engineering And Its Application, 2024)
CNC TruLaser Tube 5000 TRUMPF machine is used to perform cutting process in PT. Dempo Laser Metalindo. The quality of the cut product produced is required to have minimum roughness value, but in every cut result especially on Square Pipe St 37 material there is cutting defect. Cutting defect in the product result is surface roughness. Surface roughness can affect the cutting rate on the material, the solution to get cutting quality with minimal roughness and maximum cutting rate is to analyze the parameters that affect the response by optimizing the parameters. The parameter variables to be optimized are focus point, cutting gas pressure, nozzle distance, and laser power. This study uses Square Pipe St 37 material and the experimental design uses Taguchi Method combined with Grey Relational Analysis using orthogonal matrix L9 (34). From the results of the research that has been conducted, it was obtained that the most optimal combination of parameters for cutting rate and surface roughness is the focal point at level 2 which is 2 mm, nozzle distance at level 3 which is 1,1 mm, and laser power at level 3 which is 2700 W. The focal point parameter provides a percentage contribution of 38.60%, while the nozzle distance parameter provides a percentage contribution of 6.42%, and the laser power parameter provides a percentage contribution of 35.92%.